Synthesis and anti-parasitic activity of dehydrodieugenol B and analogues - Sear, C (2020)
This thesis describes the optimisation of a copper-catalysed biaryl ether forming reaction, and its application in the synthesis of the anti-kinetoplastid natural products, isolated from the leaves of Nectandra leucantha